The Influence of Tariffs and Non-Tariffs on Octopus Commodity Exports in Makassar - Muhammad Abi Thalib; Muhammad Dalvi Mustafa; Sitti Fakhriyyah; M. Chasyim Hasani (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2026)
This study aims to analyze how tariff and non-tariff barriers affect the export volume of octopus commodities from Makassar to destination countries. The method employed is qualitative descriptive with a case study approach, based on secondary data from relevant institutions and interviews with key informants. The analysis focuses on import tariffs in destination countries as well as non-tariff barriers in the form of SPS (Sanitary and Phytosanitary Measures) and TBT (Technical Barriers to Trade) regulations. The results indicate that although Indonesia does not impose export tariffs on octopus, destination countries still apply varying import duties, which affect the price competitiveness of the product. Non-tariff barriers have a more significant impact on exports, particularly through the enforcement of quality standards, food safety certifications, labeling requirements, and complex product traceability systems. Therefore, to enhance the competitiveness of octopus exports, it is necessary to strengthen the technical capacity of business actors, improve regulatory support, and foster synergy between the government and the private sector. Conclusion. This study concludes that increasing octopus exports to global markets requires adaptive strategies toward international regulations as well as collaboration between the government and business actors to improve product quality, legality, and distribution efficiency.